Descripción del Mildiú polvoso (Oidium sp.) en el cultivo de Achotillo (Nephelium lappaceum). - Arreaga Triviño, Luis Alfredo (2024)
In reference to the case study, the objective was determined to analyze powdery mildew (Oidium sp.) in the cultivation of Achotillo (Nephelium lappaceum). The present analysis is situated within the basic study, adopting a descriptive-bibliographic approach and a qualitative design. The descriptive-bibliographic approach focuses on the collection, analysis and synthesis of information from various bibliographic sources, with the purpose of providing a comprehensive and detailed vision of the topic in question. Regarding the results, during the investigation, an exhaustive description of the aspects related to the fungus Oidium sp. was carried out. In the cultivation of achiotillo, morphological and physiological characteristics of the fungus were identified, highlighting its appearance, life cycle and the environmental conditions that favor its development. In conclusion, powdery mildew in Achiotillo cultivation has allowed a detailed analysis of the elements involved in its vision and progress, key aspects related to the biology and ecology of the fungus have been identified, providing a comprehensive understanding of its impact on the cultivation of achiotillo. It is recommended that farmers and specialists in the cultivation of achiotillo consider incorporating varieties resistant to powdery mildew in their agricultural practices; careful seed selection can be an effective strategy to minimize the susceptibility of crops to this complication.